Coenzyme Q10 effects in neurological diseases - Rauchová, Hana (Physiological research, 2021)
Coenzyme Q10 (CoQ10), a lipophilic substituted benzoquinone, is present in animal and plant cells. It is endogenously synthetized in every cell and involved in a variety of cellular processes. CoQ10 is an obligatory component of the respiratory chain in inner mitochondrial membrane. In addition, the presence of CoQ10 in all cellular membranes and in blood. It is the only endogenous lipid antioxidant. Moreover, it is an essential factor for uncoupling protein and controls the permeability transition pore in mitochondria. It also participates in extramitochondrial electron transport and controls membrane physicochemical properties. CoQ10 effects on gene expression might affect the overall metabolism. Primary changes in the energetic and antioxidant functions can explain its remedial effects. CoQ10 supplementation is safe and well-tolerated, even at high doses. CoQ10 does not cause any serious adverse effects in humans or experimental animals. New preparations of CoQ10 that are less hydrophobic and structural derivatives, like idebenone and MitoQ, are being developed to increase absorption and tissue distribution. The review aims to summarize clinical and experimental effects of CoQ10 supplementations in some neurological diseases such as migraine, Parkinson ́s disease, Huntington ́s disease, Alzheimer ́s disease, amyotrophic lateral sclerosis, Friedreich ́s ataxia or multiple sclerosis. Cardiovascular hypertension was included because of its central mechanisms controlling blood pressure in the brainstem rostral ventrolateral medulla and hypothalamic paraventricular nucleus. In conclusion, it seems reasonable to recommend CoQ10 as adjunct to conventional therapy in some cases. However, sometimes CoQ10 supplementations are more efficient in animal models of diseases than in human patients (e.g. Parkinson ́s disease) or rather vague (e.g. Friedreich ́s ataxia or amyotrophic lateral sclerosis).
Keywords: transport elektronů; antioxidancia; Nervous System Diseases; Ubiquinone; Animals; mitochondrie; lidé; ubichinon; Mitochondrial Diseases; Electron Transport; nemoci nervového systému; Mitochondria; Antioxidants; Humans; zvířata; mitochondriální nemoci